ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN GO PUBLIC YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2009-2012 - Anggawidia Wibaselppa (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
The scoring of the profitability performance level of banking companies, that can be seen andmeasured through financial report by analyzing the influence of Capital Adequacy Ratio (CAR),Operational Burden / Operational Income, Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM)toward Return on Assets (ROA) banking profitability. The purpose of this research is to determine thescoring of the profitability performance level of banking companies. Sample taking technique usedpurposive sampling.The samples are gotten are 8 go public banks which listed in Indonesia Stock Exchange whichare private banks and BUMN banks. The analysis method in this research used double linear regressiontest and hypothesis test used t-statistic to test coefficient regression partially. The hypothesis test resultpartially (t test) shows CAR, LDR, NIM do not influence significantly toward. Banking Profitability (ROA)while BOPO influences significantly toward Banking Profitability (ROA). Adjusted R2 score in go publicbank regression model obtained 0,375. It shows how big the influence of independent variables areCAR, BOPO, LDR and NIM toward dependent ROA variable while the rest 54,5% is influenced by othervariables. If R2 score tends to 1 therefore independent variables (CAR, BOPO, LDR and NIM) becomemore influence in explaining dependent variable (ROA)